Emerging bone marrow failure syndromes- new pieces to an unsolved puzzle - Feurstein, Simone (Frontiers in Oncology, 2023)
Inherited bone marrow failure (BMF) syndromes are genetically diverse — more than 100 genes have been associated with those syndromes and the list is rapidly expanding. Risk assessment and genetic counseling of patients with recently discovered BMF syndromes is inherently difficult as disease mechanisms, penetrance, genotype-phenotype associations, phenotypic heterogeneity, risk of hematologic malignancies and clonal markers of disease progression are unknown or unclear. This review aims to shed light on recently described BMF syndromes with sparse concise data and with an emphasis on those associated with germline variants in ADH5/ALDH2, DNAJC21, ERCC6L2 and MECOM. This will provide important data that may help to individualize and improve care for these patients.